Energy transfer in color-tunable water-dispersible Tb–Eu codoped CaF2 nanocrystals. Issue 9 (16th February 2016) - Back, M.; Marin, R.; Franceschin, M.; Sfar Hancha, N.; Enrichi, F.; Trave, E.; Polizzi, S.
Abstract : The energy transfer process between Tb 3+ and Eu 3+ ions in water-dispersible CaF2 nanocrystals prepared using a simple process is reported. Fine colour control and long excited state lifetimes make the nanosystem suitable for biosensing applications. Abstract : The development of highly luminescent water-dispersible biocompatible nanoparticles is a hot topic in biomedical research. Here, we report about the study of the energy transfer process between Tb 3+ and Eu 3+ in calcium fluoride nanoparticles. Water-dispersible RE-doped nanoparticles were prepared by means of a simple synthesis route without the need for high temperature, pressure or additional surface functionalization. The structural and morphological properties were investigated by means of XRPD and TEM analysis. Optical analysis led to information about both the RE ion site symmetry in the crystalline host and the Tb 3+ and Eu 3+ excited state lifetimes, whose remarkable duration is suitable for biosensing applications. Concerning the energy transfer process, dipole–dipole interaction, with a donor–activator critical distance of about 13 Å, was identified as the most probable mechanism.